Interference avoidance routing and scheduling using multiple transceivers for IEEE 802.16 mesh network - Qasem, Yaaqob Ali Ahmed (2010)
Demand for broadband access networks has grown rapidly with the increased demand for Internet connectivity and multimedia services. Fixed broadband wireless access systems based on the IEEE 802.16 standard defines the wireless broadband access technology called WiMAX (Worldwide Interoperability Microwave Access), which introduces several interesting advantages including variable and high data rate, last mile wireless access, mesh and point to multipoint communication, large frequency range and QoS (Quality of Service) for various types of applications. Optimization of routing and link scheduling has recently become one of the leading research trends in wireless mesh networks. In centralized scheduling for IEEE 802.16 mesh networks, all packets should be transported through the Base Station (BS). The links to or from the BS become the system's bottleneck and the throughput is heavily impacted by the interference. This thesis presents an Energy/bit Minimization routing and centralized scheduling algorithms (EbMR-CS) using multi-transceiver and multi-channel for IEEE 802.16-2004 mesh networks. Here, a routing tree is constructed based on the energy/bit minimization routing (EbMR). This algorithm looks for a short path from the subscriber station (SS) node to BS, while the optimal path is achieved when the whole path has the lowest EbMR. After the route is fixed, and the traffic demanded at each node is known, the total traffic arriving at a node is centrally scheduled such that the transmission interferences can be avoided. The proposed algorithm has considered some important design metrics such as fairness, reuse timeslot, balanced load, concurrent transmissions and hop count. These algorithms have two advantages: first, they avoid the collision with neighbouring nodes. Avoiding collision, scheduled transmissions have much higher throughput than what is possible with previous approaches. Secondly, the algorithms reduce the length of scheduling, increase the channel utilization ratio (CUR) and improve the throughput of the system. The results from the single and multi-transceiver systems showed that the algorithm reduced the length of scheduling up to 43% in the multi-transceiver system and 23% in single-transceiver system. Moreover, the channel utilization ratio (CUR) is found to be improved up to 45% in the multi-transceiver system and up to 19% in single-transceiver system. In addition, the proposed algorithm improved the system throughput up to 68% in the multi-transceiver system and 28% in the single-transceiver system.